Peran Regulasi dalam Mendorong Inovasi dan Kualitas Pelayanan Publik: Tinjauan pada Sektor Pendidikan - Sabrana Ansori, Aftin; Ayu Julia Putri, Nasyah; Mukarromah, Nabila; Hayat (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2024)
This study looks into how regulations might spur innovation and raise the standard of public services provided to the education sector. This study discusses the idea of regulation, innovation theory, the idea of public service quality, and methods for gauging public service performance through the use of a literature review methodology. With limitations on nations that reflect different educational environments, the study methodology focuses on examining literature about innovation and regulation in the education sector.The study's findings demonstrate how clever and flexible policies can foster creativity and raise the standard of public services, such as education. Regulating too much, meanwhile, can make it more difficult for educational institutions to innovate. The study suggests more research be done to examine the effects of various laws and the function of technology in promoting innovation and assisting with regulatory compliance. Policymakers and practitioners can use these insights to create more flexible and useful rules in the field of education.